2015
DOI: 10.1016/j.ces.2014.11.045
|View full text |Cite
|
Sign up to set email alerts
|

Coalescence efficiency model including electrostatic interactions in liquid/liquid dispersions

Abstract: The drop size distribution is an essential process variable in liquid/liquid systems and relevant in many technical applications. It can be described by population balance equations. A coalescence efficiency model was developed to be able to describe the well-known coalescence inhibition due to changing pH value or salt concentration. The model includes the attractive van der Waals and repulsive electrostatic force according to the DLVO theory into the population balance equation framework. This DLVO model can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 47 publications
(100 reference statements)
1
18
0
Order By: Relevance
“…To avoid a violation of conservation of mass due to numerical loss of mass, a narrower normal daughter drop size distribution ( , ′ ) than proposed by Coulaloglou and Tavlarides (1977) was used (see Equation (12) in Table 1) using a standard deviation tolerance of = 5 (instead of 3) within . According to Coulaloglou and Tavlarides (1977) binary drop breakup was assumed ( = 2) (Kamp and Kraume, 2015). In some parts of this work other submodels for breakage rate and coalescence efficiency were applied (see section 1.3).…”
Section: Simulationsmentioning
confidence: 99%
See 2 more Smart Citations
“…To avoid a violation of conservation of mass due to numerical loss of mass, a narrower normal daughter drop size distribution ( , ′ ) than proposed by Coulaloglou and Tavlarides (1977) was used (see Equation (12) in Table 1) using a standard deviation tolerance of = 5 (instead of 3) within . According to Coulaloglou and Tavlarides (1977) binary drop breakup was assumed ( = 2) (Kamp and Kraume, 2015). In some parts of this work other submodels for breakage rate and coalescence efficiency were applied (see section 1.3).…”
Section: Simulationsmentioning
confidence: 99%
“…It was found that variations of the initial drop size distribution had only minor influence on the simulation results within the first milliseconds of the simulations. Hence, a Gaussian initial drop size distribution with mean value = 1 mm and standard deviation = 50 μm was used arbitrarily (Kamp and Kraume, 2015). All variables and parameters are given in SI units if dimensional; 2, of the Coulaloglou and Tavlarides (1977) model has the dimension [m -2 ].…”
Section: Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of additives with different size, wettability and shape such as surfactants, nanoparticles, ions or enzymes can severely change the interface characteristics, e.g., by affecting the breakage and coalescence phenomena due to a change from mobile to rigid interfaces , . The description of these effects often necessitates additional experimental investigations, such as the determination of the zeta potential in case of ions in liquid/liquid systems . For an exact description, all relevant characteristics of the interface need to be implemented into the respective modeling approaches.…”
Section: Interface Characterizationmentioning
confidence: 99%
“…Especially if additives or impurities barely affect the physical properties of the systems, common approaches might fail to predict the resulting droplet sizes with an acceptable accuracy since not all existing effects on droplet breakup and coalescence are taken into account. Examples are the influence of different molecular structures of surfactants with the same resulting interfacial tension or electrostatic forces induced by ions .…”
Section: Introductionmentioning
confidence: 99%